Memory devices using a mixture of MoS2 and graphene oxide as the active layer - Yin, Zongyou (2014)
A mixed film consisting of 2D MoS2 and graphene oxide (GO) nanosheets is used to fabricate memory devices. The conductive MoS2 component in the MoS2-GO film increases the film conductivity, thus facilitating oxygen migration in GO. The MoS2-GO film-based device exhibits rewritable, nonvolatile, electrical bistable switching with low switching voltage (≤1.5 V) and high ON/OFF current ratio (≈102).